ANALYSIS OF ZAKAT FUND MANAGEMENT IN EMPOWERING MSME’S OF LAZIZ MUHAMMADIYAH (LAZIZMU) AT CITY OF MEDAN - Khairunnisa Khairunnisa; Juwita Purnama Sari (Proceeding International Seminar of Islamic Studies, 2021)
Research with the title "Analysis of Zakat Fund Management in Empowering MSMEs of Lazis Muhammadiyah (LAZISMU) at Medan City." It aims to determine the zakat fund empowerment system and zakat fund management procedures in empowering MSME conducted by LAZISMU. This research method uses qualitative research methods, namely written or oral words from people and actors that can be observed. This data was obtained from literature studies, interviews, and observations to determine the zakat fund empowerment system and procedures for managing zakat funds by LAZISMU. The results obtained are the empowerment system of zakat funds conducted by LAZISMU by 1). The zakat system funds consumptive empowerment, namely by way of the provision of groceries and consumables, 2). The zakat system funds consumptive commission, namely zakat, which is realized in the condition of capital, 3). Zakat fundraising system online, namely the collection using social media such as Instagram, Facebook, Twitter, and Youtube, 4). Offline collection of zakat funds, namely the collection by making regular donors to muzakki Keywords: Zakat Fund, Management, MSME